Understanding Participant Perspectives Toward the Formation of a Participant Advisory Board Within the Reasons for Geographic and Racial Differences in Stroke Study: A National Qualitative Study - Marquita S. Brooks; Demetria Hubbard; Monika M. Safford; Emily B. Levitan; Suzanne E. Judd; Virginia J. Howard; Tomi Akinyemiju; Lonnie Hannon; Elizabeth Baquero; Madeline R. Sterling (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Although often used to inform clinical trials and public health campaigns, academic–community partnerships have been less frequently used in the context of large, national epidemiologic studies. These partnerships could enhance key aspects of the research process if appropriately leveraged. We aimed to elicit perspectives toward the formation of a participant advisory board in the REGARDS (Reasons for Geographic and Racial Differences in Stroke) study, a national prospective cohort study that enrolled >30 000 Black and White community‐dwelling adults aged ≥45 years from 48 states from 2003 to 2007 with ongoing follow‐up. Methods For this qualitative study, we used a convenience sampling approach to recruit participants. We conducted semistructured virtual interviews between May 2023 and July 2023. The Cargo and Mercer framework on academic–community partnerships in health equity research informed the interview guide and thematic analysis. Results The 18 participants had a median age of 69 years, 67% were women, 39% were Black, and 78% had a college degree or higher. Four key themes emerged: (1) trust, diversity, mutual respect, and accountability; (2) sharing the purpose and scope of research and dissemination of science; (3) engagement, formalization, and maintenance; (4) social and environmental justice and translating knowledge into action. Conclusions Participants in this large epidemiologic cohort were interested in participating in a participant advisory board and saw its benefits. Our findings can inform the formation of the REGARDS study participant advisory board, including how it should be structured and guided. This has implications for other observational cohorts interested in including participants in an advisory capacity.